Effect of Binge Eating Disorder on the Treatment Process of Bariatric Surgery - Elif Coşkun; Ezgi Devecİ; Başak İnce (Psikiyatride Güncel Yaklaşımlar, 2020)
Obesity, which continues to be widespread from past to present, is a disease to have physical, social, environmental and psychological effects. The presence of many causes of obesity and its comorbid diseases results in serious financial consequences in the diagnostic and treatment process. The methods chosen for the treatment of obesity varies according to the person's body mass index and the presence of comorbid disease. One these methods is bariatric and metabolic surgery (obesity surgery), and it is applied in the case of having additional diseases to patient’s obesity and preferences of surgeon in addition to obesity. The most important thing to know about this issue is that obesity surgery is involved in a very comprehensive treatment. After surgery, the person should be followed with a multidisciplinary approach by an internal medicine specialist, a dietician specializing in bariatric surgery, a psychiatrist or psychologist specializing in nutrition and eating disorders. One of the most important problems encountered before and after the operation, which may adversely affect the success of the operation, is binge eating disorder. This article focuses on how binge eating disorder and mood influence obesity surgery.